Bound to work outside home: the "bóia fria" women on the go - Saffioti, Heleieth I. B.; Ferrante, Vera L. S. B. (Universidade Estadual Paulista / UNESP, 2009)
This paper, which is the result of a research done among families of workers region of Araraquara, SP, discusses the woman's participation in the revindicatory movements of people, trying to bring into existence that participation which has become invisible by the circumstances.